The Shikhara of the Mahishasuramardini Temple - Temples of India Project Team (Jio Institute, 2024)
The shikhara (superstructure) of the garbhagriha (sanctum sanctorum) is carved in the latina (mono-spired) style with navabhumis (nine tiers). The shikhara is intricately carved with the jala of chaitya arches. A dhvajadharaka (flag bearer), a structure to hold the dhavja (flag), is also depicted at the top, on the rear side of the shikhara.